Regional wall motion abnormalities predict culprit lesions in patients presenting with acute chest pain. (14th October 2021) - Roggel, A; Hendricks, S; Dykun, I; Balcer, B; Al-Rashid, F; Risse, J; Kill, C; Totzeck, M; Rassaf, T; Mahabadi, A A
Abstract: Background: Current ESC guidelines for non-ST-segment elevation myocardial infarction suggest the utilization of echocardiography in patients with inconclusive initial electrocardiography and cardiac enzymes. Besides detection of alternative pathologies associated with chest pain, echocardiography can screen for wall motion abnormalities (WMA) as sign of myocardial necrosis. Purpose: We evaluated the ability of the assessment of regional WMA, detected via transthoracic echocardiography, to predict the presence of culprit lesions in patients presenting with acute chest pain to the emergency department. Methods: In this prospective single-centre observational cohort study, we included consecutive patients presenting to the emergency department of our University Hospital with acute chest pain, suggestive of an acute coronary syndrome, between December 2018 and August 2020. Patients with ST-elevation myocardial infarction, hemodynamic instability, or known coronary artery disease were excluded. As part of initial workup, patients received bedside echocardiography for the assessment of regional WMA by a dedicated study physician, blinded to all patients' characteristics. The primary endpoint was defined as the presence of culprit lesions as detected in subsequent invasive coronary angiography, requiring coronary revascularization therapy. Logistic regression analysis was performed in different models adjusted for traditional cardiovascular risk factors, cardiac biomarkers as well as established risk scores. Area under the receiver operating characteristics curve (AUC) was calculated to assess a potential improvement in the prediction of culprit lesions. Results: Overall, 657 patients (age 58.06±18.04 years, 53% male) were included in our study. WMA were detected in 76 patients (11.6%). Patients with WMA were older (66.92±13.85 vs. 56.90±18.21 years, p<0.001), had significantly higher Troponin-levels (18.5 [6.0; 91.5] vs. 6.0 [6.0; 15.0], p<0.001) and higher blood pressure (139.0±19.29 vs. 135.1±19.21, p=0.04). WMA were significantly more frequent in patients reaching the primary endpoint (26.2% vs. 7.6%, p<0.001). In multivariable regression analysis, the presence of WMA was associated with 3-fold increased odds of the presence of culprit lesions (3.41 [1.99–5.86], p<0.001). Adding WMA to a multivariable model containing the TIMI risk score, cardiac biomarkers and traditional risk factors significantly improved the AUC for prediction of obstructive coronary artery disease (0.777 to 0.804, p=0.009). Conclusion: WMA strongly and independently predict the presence of culprit lesions in patients presenting with acute chest pain to the emergency department. Our results suggest that routine bedside echocardiography for assessment of WMA in emergency department may improve diagnostic algorithms in suspected acute coronary syndrome. FUNDunding Acknowledgement: Type of funding sources: None.